THE EFFECTS OF DIFFERENT CHILLING METHOD AND STORAGE TIME ON THE ORGANOLEPTIC QUALITY OF FRESH SKIPJACK TUNA - Christina Litaay; Sugeng Hari Wisudo; John Haluan Haluan; Bambang Harianto (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Fish freshness plays an importantant role in determining quality of fish product. Organoleptic is one of sensorik method for determining fish freshness. The fish deterioration mainly affected by temperature. This study aimed to determine the best method for determining organoleptic quality of skipjact tuna based on chilling methods and storage time. Fish sampling were taken from the Seram Sea, Maluku Province. Chilling methods was done by the different ratio between the ice and fish: first was without using ice, second was ratio 1:1 and the third was ratio 1:2. The time storage were 0, 2, 4, and 6 hours.The results showed that chilling methods ratio between the ice and fish of 1:1 with 6 hours storage time provided the best organoleptic quality with eye 8.87, mucus 8.83, gill 8.67, meat 8.73, odour 8.80, and texture 8.86. Keywords: chilling methods, organoleptics, skipjact tuna